The effect of assistive devices on gait patterns in Parkinson’s disease : a pilot study - Martins, Inês B. (2019)
Abstract of poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Monte de Caparica, Portugal